Creatividad percibida por estudiantes en el proyecto de diseño de interiores - Guzmán Guerra, Gema Rocío (UNIVERSIDAD DE SONORA, 2023)
In the interior design studio, creativity is an essential component, since it is where the student explores diverse skills according to professional practice, aimed at providing solutions to interior spaces in an attractive and efficient way. The research objective is to identify notions about the creativity concept among students, as well as characteristics associated with interior design projects that are considered outstanding in the academic context. Work was done with a non-probabilistic sample chosen at convenience according to the specific UACJ students’ profile in a current design studio subject; the approach was carried out through the application of a survey, elaborated based on topics identified by experts in the development of interior design projects. From the results’ statical analysis adjectives associated with creativity were identified, highlighting imaginative, ingenious, and novel, as well as the main correlations between the variables in question. Three important components associated to creativity also stood out: relevance, innovation, and  authenticity. It is essential to identify the perception of creativity from the university context, to establish a definition that integrates the indicators associated with it in the interior design projects and to verify the expected results of the design proposals.